Precipitate synthesis of BaMoO 4 and BaWO 4 nanoparticles at room temperature and their photoluminescence properties - Phuruangrat A. (2014)
The uniform BaMoO 4 and BaWO 4 nanoparticles (NPs) have been successfully synthesized by solution route - the direct precipitation of Ba(NO 3) 2 and Na 2MO 4 (M = Mo and W) in ethylene glycol under 24 h stirring. The XRD patterns and SEM images proved that the products were tetragonal structured BaMoO 4 and BaWO 4 with uniform round nanoparticles. Shape, average particle size and particle-size distribution of products were analyzed by TEM - showing the round nanoparticles with the average size of 31.52 ± 4.65 nm for BaMoO 4, and 59.77 ± 9.61 nm for BaWO 4. The room temperature photoluminescence (PL) indicated that the products have strong blue emission centered at 441 nm - excited with 280 nm wavelength for BaMoO 4 NPs, and strong violet emission centered 378 nm - excited with 344 nm wavelength for BaWO 4 NPs. These PL behaviors attributed the existence of intrinsic transitions in the [MO 4] 2- (M = Mo and W) tetrahedrons of their crystal lattices. © 2012 Elsevier Ltd. All rights reserved.